L'image de la Guerre civile espagnole dans la bande dessinée entre 1936 et 1975-I - Michel Matly (Cahiers de Civilisation Espagnole Contemporaine)
This paper is the first of two that present a quick overview of the representation of Spanish Civil War in comics from the beginning of the conflict in 1936 up to Franco's death in 1975. This first part investigates Spanish comics during wartime and a second one will deal with other countries' comics in the same period, as well as Spanish and foreign comics during the following years of the Francoist dictatorship. During the conflict, both opponents extensively used comics with fairly different purposes and tones. The Franco's camp used them for propaganda and mudslinging the enemy, in a rather restrained tone in the case of the extreme-right Phalange, more radical and full of hatred in the case of the Catholic Church. The governmental camp used comics in trench magazines to entertain and educate soldiers, in political newspapers to reject war's responsibility on foreign countries and in comic magazines to reduce anguishes of the juvenile public in front of war events.